ANALISIS PERBANDINGAN KEPUASAN NASABAH BANK SYARIAH DENGAN BANK UMUM KONVENSIONAL DI SURABAYA - Sarwani, Sarwani; Herawati, Andry; Listyawati, Liling (JHP17 (Jurnal Hasil Penelitian), 2019)
Quality of service is essential for growth and success in the banking sector, as servicebecomes an increasingly important factor in determining market share and bank profitability.Therefore, the banking sector is required to make improvements as well as improving thequality of service to regain public confidence. Both Conventional and Sharia Banks compete toprovide the best services so that the needs or expectations of customers are met. If the customeris satisfied with the services provided, then the customer will be loyal to the bank. In order forcustomer satisfaction to be realized, the bank must have the ability to provide the best service.Of course from these services will arise a variety of customer ratings. This study aimed toanalyze the comparison of customer satisfaction of Sharia Bank and common conventional bankto the quality of service provided. The analysis model used is Importance PerformanceAnalysis, whereas to know whether there is any difference of satisfaction between commonconventional bank customer with sharia bank customer, U Mann-Whitney non parametric test istwo independent samples. To facilitate the analysis, the researchers used SPSS program. Basedon the Importance Performance Analysis that has been done, it can be seen that the service ofboth banks is quite satisfactory and has met the expectations of customers. While from result ofanalysis of U Mann-Whitney non parametrik two independent samples obtained that there isdifference of satisfaction between common conventional bank customer with customer of shariabank.Keywords : Customer Satisfaction, Bank Syariah, Common Conventional Banks